The neurobiology of human fear generalization: meta-analysis and working neural model. (September 2021) - Webler, Ryan D.; Berg, Hannah; Fhong, Kimberly; Tuominen, Lauri; Holt, Daphne J.; Morey, Rajendra A.; Lange, Iris; Burton, Philip C.; Fullana, Miquel Angel; Radua, Joaquim; Lissek, Shmuel
Highlights: The first meta-analysis of fMRI studies assessing generalized conditioned fear is provided. Cingulo-opercular, frontoparietal, and midbrain loci code for generalization, with activations positively scaling to danger-cue resemblance. Default mode regions instantiate inverse generalization, with activations negatively scaling to danger-cue resemblance. Meta-analytic results are integrated into an updated neural account of conditioned fear generalization. Abstract: Fear generalization to stimuli resembling a conditioned danger-cue (CS+) is a fundamental dynamic of classical fear-conditioning. Despite the ubiquity of fear generalization in human experience and its known pathogenic contribution to clinical anxiety, neural investigations of human generalization have only recently begun. The present work provides the first meta-analysis of this growing literature to delineate brain substrates of conditioned fear-generalization and formulate a working neural model. Included studies ( K = 6, N = 176) reported whole-brain fMRI results and applied generalization-gradient methodology to identify brain activations that gradually strengthen (positive generalization) or weaken (negative generalization) as presented stimuli increase in CS+ resemblance. Positive generalization was instantiated in cingulo-opercular, frontoparietal, striatal-thalamic, and midbrain regions (locus coeruleus, periaqueductal grey, ventral tegmental area), while negative generalization was implemented in default-mode network nodes (ventromedial prefrontal cortex, hippocampus, middle temporal gyrus, angular gyrus) and amygdala. Findings are integrated within an updated neural account of generalization centering on the hippocampus, its modulation by locus coeruleus and basolateral amygdala, and the excitation of threat- or safety-related loci by the hippocampus.